Influence of welding sequences on residual stress and deformation of U-rib components fabricated by laser-arc hybrid welding - Shaoning Geng; Yuantai Li; Ping Jiang; Yilin Wang; Jun Jin; Chu Han (Journal of Materials Research and Technology)
This paper aims to investigate the influence of welding sequences on welding induced residual stress and deformation of U-rib components fabricated by laser-arc hybrid welding through experimental and numerical methods. A thermo-elastic-plastic finite element model was developed to capture the complex thermal and mechanical behavior during the U-rib welding process. The model was validated by neutron diffraction testing of residual stress in U-rib joints focusing on a typical continuous sequential welding condition. To further quantify the residual stress and residual deformation induced by different welding sequences, eight models of continuous and segmental welding sequences are conducted. The results show that the experimental and numerical results are in general agreement in terms of temperature field, melt pool morphology, residual stress, and deformation. The neutron diffraction validation shows an S-shaped curve along the potential crack propagation path in the joint and emphasizes the reliability of the model. Welding sequence has effect on the longitudinal stress in the weld and deck top of the U-rib joints but little influence on the transverse residual stress. The continuous welding sequence shows a bimodal pattern with almost identical peaks for both welds, while the segmental welding sequences clearly exhibit one peak high and one peak low. Segmental double-sided simultaneous welding with the “End→Middle←End” path significantly reduces residual deformation, decreasing the maximum bending deformation by approximately 33% compared to continuous sequential welding. This study provides theoretical and technical guidance for improving high quality fabrication of U-rib components and large welded structures using laser-arc hybrid welding.